Flexible Stable Solid‐State Al‐Ion Batteries - Yu, Zhijing; Jiao, Shuqiang; Li, Shijie; Chen, Xiaodong; Song, Wei‐Li; Teng, Teng; Tu, Jiguo; Chen, Hao‐Sen; Zhang, Guohua; Fang, Dai‐Ning (Advanced functional materials, 2019)
Rechargeable aluminum‐ion batteries (AIBs) are regarded as promising candidates for post‐lithium energy storage systems (ESSs). For addressing the critical issues in the current liquid AIB systems, here a flexible solid‐state AIB is established using a gel‐polymer electrolyte for achieving robust electrode–electrolyte interfaces. Different from utilization of solid‐state systems for alleviating the safety issues and enhancing energy density in lithium‐ion batteries, employment of polymeric electrolytes mainly focuses on addressing the essential problems in the liquid AIBs, including unstable internal interfaces induced by mechanical deformation and production of gases as well as unfavorable separators. Particularly, such gel electrolyte enables the solid‐state AIBs to present an ultra‐fast charge capability within 10 s at current density of 600 mA g−1. Meanwhile, an impressive specific capacity ≈120 mA h g−1 is obtained at current density of 60 mA g−1, approaching the theoretical limit of graphite‐based AIBs. In addition to the well‐retained electrochemical performance below the ice point, the solid‐state AIBs also hold great stability and safety under various critical conditions. The results suggest that such new prototype of solid‐state AIBs with robust electrode–electrolyte interfaces promises a novel strategy for fabricating stable and safe flexible ESSs. Flexible stable solid‐state Al‐ion batteries are constructed using the gel‐polymer electrolyte, Al anode, and graphite cathode. The novel polymeric electrolyte substantially promotes the overall energy storage performance via addressing the unstable internal interfaces induced by mechanical deformation and production of gases as well as unfavorable separators in the liquid systems, suggesting new strategies for achieving advanced flexible energy storage devices.